Idiopathic Neuralgic Amyotrophy: A Rarely Documented Disease in Children (Bangladesh Journal of Child Health, 2022)
Idiopathic Neuralgic amyotrophy (INA) is a neurological disease that occurs in all age groups. It is characterized by sudden onset of pain and subsequent weakness followed by atrophies of arm and shoulder muscles. But in children, it is uncommon and has a diverse clinical spectrum and etiology. Diagnosis is often delayed or even missed. Its treatment protocol and prognosis are still controversial. We herein describe three cases of INA with a thorough review of thepreviously reported cases in children. This will provide an overview of the pediatric phenotype and prognosis.BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 116-119